Theoretical and Experimental Study on Rotary Compressor with Double Vapor Injection and Its System. Issue 1 (September 2021) - Wei, H J; Xu, J; Yu, B; Yang, O X; He, S G; Zhao, H H; Hu, Y P
Abstract: This paper takes three kinds of double vapor injection compression cycle as the research object, that is, the two-stage compression cycle with double vapor injection on low-pressure cylinder and intermediate of two cylinders (Cycle A), the two-stage compression cycle with double vapor injection on high-pressure cylinder and intermediate of two cylinders (Cycle B), and the three-stage compression cycle with double vapor injection (Cycle C). According to the law of conservation of mass and energy, the thermodynamic analysis model of each cycle was established, and the influence of saturation temperature of double vapor injection on the performance of each cycle was analyzed. The theoretical analysis results indicated that the refrigeration capacity of cycle A, cycle B and cycle C increase by 12.5%, 3.5% and 4.6%, respectively, and COP of that increase by 3.09%, 2.23% and 3.22%, respectively, compared with that of single stage compression cycle. Based on cycle A, a single-machine two-stage rotary compressor with double vapor injection and its heat pump air conditioning are made. The experimental results showed that, the heating capacity of cycle A can increase by 14.6% when the heating COP is equivalent, and the heating COP can increase by 4.4% when the heating capacity is equivalent, compared with the two-stage compression cycle with single vapor injection, under the –15°C ambient temperature heating condition.